A review of odour impact criteria in selected countries around the world. (February 2017) - Brancher, Marlon; Griffiths, K. David; Franco, Davide; de Melo Lisboa, Henrique
Abstract: Exposure to environmental odour can result in annoyance, health effects and depreciation of property values. Therefore, many jurisdictions classify odour as an atmospheric pollutant and regulate emissions and/or impacts from odour generating activities at a national, state or municipal level. In this work, a critical review of odour regulations in selected jurisdictions of 28 countries is presented. Individual approaches were identified as: comparing ambient air odour concentration and individual chemicals statistics against impact criteria (maximum impact standard); using fixed and variable separation distances (separation distance standard); maximum emission rate for mixtures of odorants and individual chemical species (maximum emission standard); number of complaints received or annoyance level determined via community surveys (maximum annoyance standard); and requiring use of best available technologies (BAT) to minimize odour emissions (technology standard). The comparison of model-predicted odour concentration statistics against odour impact criteria (OIC) is identified as one of the most common tools used by regulators to evaluate the risk of odour impacts in planning stage assessments and is also used to inform assessment of odour impacts of existing facilities. Special emphasis is given to summarizing OIC (concentration percentile and threshold) and the manner in which they are applied. The way short term odour peak to model time-step mean (peak-to-mean) effects is also captured. Furthermore, the fundamentals of odorant properties, dimensions of nuisance odour, odour sampling and analysis methods and dispersion modelling guidance are provided. Common elements of mature and effective odour regulation frameworks are identified and an integrated multi-tool strategy is recommended. Graphical abstract: Highlights: Odour regulations from 28 countries are reviewed. Worldwide, odours are regulated by different approaches. Limits of odour concentration in ambient air differ substantially among jurisdictions. The international regulatory framework on odour impact criteria calculated by dispersion models is summarized. An integrated multi-tool strategy for odour impact assessment is recommended.